2011
DOI: 10.1590/s0034-89102011000200016
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rates and predictors in women with HIV/AIDS in Rio de Janeiro, Southeastern Brazil

Abstract: OBJECTIVE:To assess incidence and predictors of fi rst pregnancy among women with HIV/AIDS. METHODS:Prospective cohort study was conducted in Rio de Janeiro, southeastern Brazil, between 1996 and2003. This study comprised 225 women with HIV/AIDS followed up until their fi rst pregnancy or fi rst censored event (hysterectomy, tubal ligation, menopause, 50 years of age, loss to follow-up, death or the end of December 2003). Pregnancy and abortion rates were estimated, and Cox proportional hazards models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
6
17
0
Order By: Relevance
“…Overall, the information collected in this study on repeat pregnancy among women with HIV infection confirms some of the findings obtained by others and offers new insights: as already shown by others, repeat pregnancy in women with HIV infection was associated with younger age , foreign country of origin , and parity (no prior pregnancies) . We also showed that women with subsequent pregnancies were more likely to have been diagnosed with HIV infection in the current pregnancy, but also more likely to have a first pregnancy ending in no live birth, a finding common to the study by Kreitchmann et al .…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the information collected in this study on repeat pregnancy among women with HIV infection confirms some of the findings obtained by others and offers new insights: as already shown by others, repeat pregnancy in women with HIV infection was associated with younger age , foreign country of origin , and parity (no prior pregnancies) . We also showed that women with subsequent pregnancies were more likely to have been diagnosed with HIV infection in the current pregnancy, but also more likely to have a first pregnancy ending in no live birth, a finding common to the study by Kreitchmann et al .…”
Section: Discussionsupporting
confidence: 90%
“…There are few studies that examine the association between HIV and induced abortion [42], especially regarding the comparison between WLHA and WNLHA [13][15], [38]. Moreover, the scenario in which these studies were performed is different.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, other studies have focused on specific pregnancies, analyzing abortion and HIV status in each pregnancy (e.g., last pregnancy before and first pregnancy after HIV diagnosis [11], [12], or pregnancies that occurred during the study period [13], [14], [35], [38]). …”
Section: Introductionmentioning
confidence: 99%
“…To study the natural history of HIV infection in women, a prospective open cohort was established at IPEC in 1996. Study visits occur every 6 months; sociodemographic, behavior, reproductive, gynecologic and laboratory data are collected using structured questionnaires [20], [21].…”
Section: Methodsmentioning
confidence: 99%